Study on process parameters effects to burr height in drilling of Aluminium 6061 alloy sheet on CNC milling machine - Nguyen Huu Tho; Nguyen V. A. Duy; Dinh Tien Dung; Nguyen M. Huy; Nguyen V. Thanh; Jannifar Jannifar (Jurnal POLIMESIN, 2022)
Productivity and quality of drilling are also of interest, have been paid more attention on the size of burr through the cleaning process. The presence of burr on drilled workpieces creates problems not only in the processing but also in the assembly line, affecting the accuracy of the assembly. Many factors have significant impacts on the burr height such as spindle speed, cutting feed and drill bit diameter. In this paper, the experiment investigation of those process parameters to burr height is implemented, then Taguchi-based approach is used to determine the influence density of each factors. Moreover, artificial neural network model is applied to predict the burr height based on the three input factors. The experiment results showed that the two most important factors affecting the burr are the speed of the spindle and the feed rate. The factors realized to be significant for burr formulation such as an 8 mm drill bit diameter, a CNC spindle speed of 2500 rpm, and feed rate of 70 mm/rev, which will result in the smallest output in terms of the height of the obtained burr is 0.12792 mm.